Electrocatalytic Activity of 3‐Dimensional Ordered Macroporous Gold Electrode‐Based Lactate Biosensors Platforms as a Function of Pore Layer Number. Issue 1 (21st November 2012) - Gamero, M.; Fierro, J. L. G.; Lorenzo, E.; Alonso, C.
Abstract We report the electrocatalytic response of a lactate biosensor, based on a 3‐dimensional ordered macroporous (3DOM) gold electrode, as a function of the pore layer number. The biosensor was developed by covalent immobilization of lactate oxidase (LOx) to a self‐assembled monolayer of dithiobis‐N‐succinimidyl propionate (DTSP). The binding of DTSP to the gold surface was studied by X‐ray photoelectron spectroscopy (XPS), indicating the existence of SAu bonds. The DTSP coverage and the different steps followed in the construction of the biosensor were examined by electrochemical impedance spectroscopy (EIS). The catalytic response to a 14 mM lactate concentration, increased linearly with the pore layer number of the 3DOM gold electrode, reaching a value 3 times higher, than for polycrystalline gold electrodes, for 7.5 layers.